The Analysis of Function and Poetry Content of Traditional Marriage in Seusina Village Community, Sikka Regency - Robertus Adi Sarjono Owon; Nanda Saputra (Britain International for Academic Research (BIAR-Publisher), 2021)
This study aims to analyze the function and poetry content of traditional marriage in Seusina Village community, Kewapante District, Sikka Regency, NTT Province. Traditional poetry as an oral tradition contains teachings and values of life that are passed down from generation to generation. The method used in this research is descriptive qualitative with content analysis. Sources of data in the study were informants who met certain criteria and the data in the study were traditional old utterances in the form of word strands that form lines and stanzas. The data validation used the method of triangulation technique, namely by comparing the results of observations in the traditional wedding ceremony of the Seusina Village community. The results showed that the traditional marriage poetry of the Seusina Village community functions as a means of education (didactic) and a means of teaching about good and bad things (morality). The contents of the traditional marriage poetry of the Seusina Village community include strengthening the values of politeness, generosity, patience, and tenacity.